(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2023)
To address the issue of the growing need for measuring populist attitudes, researchers have proposed several instruments with different theoretical backgrounds in conceptualizing the construct. This study aimed to verify the psychometric properties of the recently developed Three-dimensional populist scale by Shultz and her associates. As opposed to scales which define populist attitudes as uni-dimensional constructs, this one is based on the presumption that it is a latent higher-order construct with three distinct first-order dimensions. The convenient sample was comprised of 535 participants, all ethnic Macedonians (53.1% women) from 25 urban (52.6% from the capital city) and 15 rural areas of the country, with average age M = 36.2 (SD = 12.4) and mostly (65%) with completed high school. All participants voluntarily answered the set of selected instruments which included two populist attitudes scales, several other scales the measure related variables and demographic data. The psychometric characteristics of the instrument in this particular cultural context were explored by performing item-analysis, factor analysis and testing the proposed hypotheses generated on the basis of previous relevant research. Results confirmed the three-dimensional structure of the Shultz’s scale with excellent fit indicators, while the Alpha coefficients showed acceptable reliability of the scale and its subscales. The construct dimensions exhibit significant associations with other measures expected to be related to populist attitudes endorsement. It was concluded that the Shultz et al. three-dimensional scale on populist attitudes translated in Macedonian is adequate to be used as a measure of this variable and that its efficacy for predicting electoral choices should be further scrutinized.